Characterization of Lipoteichoic Acids as Lactobacillus delbrueckii Phage Receptor Components - Räisänen, Liisa (American Society for Microbiology, 2004)
Lipoteichoic acids (LTAs) were purified from Lactobacillus delbrueckii subsp. lactis ATCC 15808 and its LL-H adsorption-resistant mutant, Ads-5, by hydrophobic interaction chromatography. L. delbrueckii phages (LL-H, the LL-H host range mutant, and JCL1032) were inactivated by these poly(glycerophosphate) type of LTAs in vitro in accordance to their adsorption to intact ATCC 15808 and Ads-5 cells.